Tanjung enim tourism map website based on geographic information system using leaflet javascript - Putra Putra; Astrid Fadhilah (Institute of Computer Science (IOCS), 2023)
Tanjung Enim is one of the villages in Lawang Kidul sub-district, Muara Enim Regency, including a geographical area with cross-provincial coverage that has potential tourism resources and tourist attractions. However, the large potential of tourist attractions in Tanjung Enim is not matched by the development of sufficient geographic information system technology. So not many tourists and the general public know about potential tourist attractions. Geographic Information Systems in the form of websites are designed to search for tourist locations and guide tourists to their destination. WebGIS creation using the Leaflet Javascript Library and Open Street Map for map digitization, HTML5, and CSS3 programming languages. The result of this research is the development of a WebGIS which contains 10 tourist attractions with tourist attraction categories, namely natural tourism, artificial tourism, cultural tourism, and culinary tourism. This WebGIS displays information on tourist destinations, history, product details, and presents information interactively to users. The results of functional testing on desktop and mobile devices show that the percentage of system feasibility is 100% with a very good rating